2006
DOI: 10.1590/s1135-57272006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de atención a los síntomas somáticos sin causa orgánica: de los trastornos fisiopatológicos al malestar de las mujeres

Abstract: Somatic symptoms of no identifiable organic cause remain medically unexplained and have been delved into to only a limited degree from a biologicist conception of health. Different critical theories study contextual, gender-related and subjective factors for Somatic Symptoms of No Identifiable Organic Cause and their care models. This study has been aimed at reviewing published Spanish studies (1995-2002) exploring explanatory SSNIOC's by relating them to the underlying health theories. A search was run in Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
18

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 41 publications
0
22
0
18
Order By: Relevance
“…Our study followed a similar approach to others which have demonstrated that a change in the focus of activities and beliefs about the disease could reduce symptoms and improve pain tolerance and functional status (Friedberg, Williams, & Collinge, 2012;Thieme & Turk, 2012). According to Velasco, Ruiz, and Alvarez-Dardet (2006), patients in their sample spoke of difficulties in fulfilling the traditional female gender role.…”
Section: Discussionmentioning
confidence: 90%
“…Our study followed a similar approach to others which have demonstrated that a change in the focus of activities and beliefs about the disease could reduce symptoms and improve pain tolerance and functional status (Friedberg, Williams, & Collinge, 2012;Thieme & Turk, 2012). According to Velasco, Ruiz, and Alvarez-Dardet (2006), patients in their sample spoke of difficulties in fulfilling the traditional female gender role.…”
Section: Discussionmentioning
confidence: 90%
“…The same thing applies to other pathologies affecting women such as endometriosis or those that are largely diagnosed, as in anxiety and depression, which have been assigned to women in a historical sense due to a supposed greater mental frailty and vulnerability as far as the female gender is concerned (3033). The classification of diseases and syndromes is in accordance with biomedical paradigms based on physiopathology and an objective position (7) and, consequently, the biologistic approach is unable to provide answers when changes found in signs and symptoms are not brought about by organic causes (34). As a result, diseases such as FM remain outside the biomedical classical ‘system’, which aims to identify the organic cause of disease and treat symptoms with drugs (35).…”
Section: Discussionmentioning
confidence: 99%
“…La depresión es un grupo heterogéneo de trastornos afectivos que se caracteriza por un estado anímico decaído, disminución del disfrute, apatía y pérdida de interés por el trabajo, sentimientos de minusvalía, insomnio, anorexia e ideación suicida 34. Entre los factores que contribuyen a su incremento según la OMS, están: la longevidad, acelerados cambios psicosociales, incremento de enfermedades crónicas, altos niveles de estrés y ansiedad, antecedentes, tanto personales como familiares, de depresión y suicidio 35 . Otros factores asociados incluyen: bajo nivel socioeconómico, tabaquismo, consumo de sustancias psicoactivas, alcoholismo y disfuncionalidad familiar 34 .…”
Section: Discussionunclassified